Jerusalem (NHB Modern Plays). - Butterworth, Jez (Nick Hern Books, 2012)
A comic, contemporary vision of life in England's green and pleasant land. Winner of the Evening Standard Award for Best Play, and the Critics Circle and Whatsonstage.com Awards for Best New Play. On St George's Day, the morning of the local country fair, Johnny 'Rooster' Byron, local waster and Lord of Misrule, is a wanted man. The council officials want to serve him an eviction notice, his son wants to be taken to the fair, a vengeful father wants to give him a serious kicking, and a motley crew of mates wants his ample supply of drugs and alcohol. Jerusalem premiered at the Royal Court Theat.